Prognostic Value of Labyrinthine 3D-FLAIR Abnormalities in Idiopathic Sudden Sensorineural Hearing Loss - Lee, J.I.; Yoon, R.G.; Lee, J.H.; Park, J.W.; Yoo, M.H.; Ahn, J.H.; Chung, J.W.; Park, H.J. (American Journal of Neuroradiology, 2016)
BACKGROUND AND PURPOSE: According to recent research, modern MR imaging can detect the presense of abnormalities on labyrinthine. Our aim was to report the patterns and prognostic role of abnormal findings on labyrinthine imaging in patients with sudden sensorineural hearing loss.MATERIALS AND METHODS: This study comprised 113 patients who were diagnosed with unilateral sudden sensorineural hearing loss and underwent 3T MR imaging, including pre-/postcontrast 3D fluid-attenuated inversion recovery and T1-weighted imaging. We analyzed abnormalities on MR imaging and correlated them with audiometric results.RESULTS: Thirty-one (27%) patients showed abnormal findings on labyrinthine MR imaging in the affected ear. The initial/final hearing levels of the MRI+ group (91 ± 25/73 ± 27 dB hearing loss) were significantly worse than those of the MRI− group (69 ± 30/48 ± 24 dB hearing loss). The incidence of abnormalities on labyrinthine MR imaging was significantly lower (3 of 40, 8%) in 40 patients with initial mild-to-moderate hearing loss than in those with profound hearing loss (16 of 34, 47%). Considering hearing improvement by the Siegel criteria, the rate of complete or partial recovery was significantly higher in the MRI− group (34%) than in the MRI+ group (10%). In patients with initial severe or profound hearing loss, the MRI− group showed greater hearing improvement (38 ± 21 dB) than the MRI+ group (23 ± 22 dB).CONCLUSIONS: Abnormalities on labyrinthine MR imaging were found in 27% of patients with sudden sensorineural hearing loss. The initial hearing loss was worse in the MRI+ group than in the MRI− group. In patients with initial severe and profound hearing loss, the presence of abnormalities on labyrinthine MR imaging indicated a poor prognosis.DPOAEdistortion product otoacoustic emissionsHLhearing lossPTApure-tone averageSSNHLsudden sensorineural hearing loss